Luxación congénita de cadera. Displasia evolutiva de la cadera (DEC) - Nazer H., Julio; Hübner G., María Eugenia; Cifuentes O., Lucía; Mardones B., Camila; Pinochet M., Camila; Sandoval S., M. Loreto (Revista Hospital Clínico Universidad de Chile, 2009)
The change of denomination of congenital hip luxation for evolutionary hip displasia is defined and explained, it incluyes luxation, subluxation and hip instability. The frequencies of this pathology in the Clinical Hospital of the University of Chile is reported. The finds of significant major frequency in female newborn children, breech presentation and left hip are communicated. The family base of this pathology is confirmed. The recommendations of the experts’ Committee of the American Academy of pediatrics and those of the health department of Chile are given. It is emphasized that the diagnosis must be as precocious as possible and that the best method of diagnosis is Ortolani’s or Barlow maneuver, done by a professional of experience. It is indicated the oportunity in which the ultrasound scan and the hip X-ray must be done, also the recommended treatment. The use of the double diaper is scorned and its possible sequels are commented.